MOTIVATIONS ET IMPLICATIONS DE L’ADOPTION DES SYSTÈMES DE MANAGEMENT DE LA QUALITÉ : CAS DU MAROC - Abderrassoul, Lehadiri; Omar, Rah (European Scientific Journal, ESJ, 2014)
The analysis of motivations for the transition to the quality certification is a central issue for organizations, the competitiveness and their survival depends on it. Previous work has demonstrated the importance of this approach and has identified the major causes. In Morocco, the work in management on this topic are rare, hence the interest of this research. This work focuses on the determinants of the adoption of quality management systems, and the impact of this innovation on managerial performance. After a review of the literature, a conceptual framework is adopted to describe the process of adoption of these tools and their impact on the modernization of enterprises in the textile and clothing sector.